The Impact of Government Expenditure on Economic Growth in Malaysia - Siti Nur Ayunie Binti Zawawi; Chong Siew Huay; Tun Yin Li (Information Management and Business Review, 2024)
This study experimentally investigates the relationship between economic growth and government spending in Malaysia from 1990 to 2022 using time series data. The study analyzes the impact of total government spending on economic growth, covering housing, healthcare, social services, military, and education while identifying which sector has the most effect on economic growth. The Autoregressive Distributed Lag (ARDL) method is employed to evaluate the effects of these expenditures. The findings demonstrate that, in the short run, all variables significantly affect economic growth, hence refuting the null hypothesis. However, only trade openness and labor spending positively impact long-term economic growth. Research indicates that housing and education expenditures are the primary long-term drivers of economic growth in Malaysia. The data suggest that the Malaysian economy contradicts the Keynesian theory, as less government spending appears to improve the real GDP growth rate. The inverse relationship between government spending and economic growth indicates that government expenditure may not be the primary catalyst for economic growth, hence supporting Wagner’s law. These findings provide policymakers with essential insights for optimizing government spending to improve economic development results.